Infografia interativa: mapeamento e catalogação da produção criativa do artesanato paraibano - Chaudhry, Alia Nasim (2018)
Handicraft is traditionally a relevant cultural expression. It is a way to represent folklores, languages and lifestyle. In the face of technological development, this cultural representation brings to the product a new creative value. This research aims to map and catalog the production of handicrafts in the State of Paraíba – Brazil, through interactive infographics. Using digital tools, this work mine national and state databases related to the Handicraft of Paraíba and transform them into infographics through Tableau data software. These infographics will be the basis used for the creation of sites, which in turn will provide information for the dissemination of the Brazilian handicraft through digital media. This information movement is essential to bring investments and new public policies for the maintenance of the sector.